DENTAL CARIES MANAGEMENT IN YOUNG CHILDREN WITH INTERIM THERAPEUTIC RESTORATION - Novita Sukma; Badi Soerachman (Fakultas Kedokteran Gigi Unjani, 2022)
ABSTRACT Caries are the most common case in every individual, including children who are still at an early age. Caries in primary teeth can occur in the early period of tooth eruption, which begins with the presence of white spot lesions. Dental caries are known as Early Childhood Caries (ECC) at an early age. ECC is used for caries in primary teeth up to 71 months. Many factors trigger the occurrence of ECC. Early treatment is very important to prevent comprehensive damage. Usually, the operator will face conditions that are not conducive to treatment. Young children generally will behave uncooperatively, have very high mobility, cry, and have difficulty opening their mouths, so it will be difficult for the operator to give treatment. One of the most therapy is dental restoration. The treatment approach will depend on the severity of the case; treatment can be in the form of non-operative therapy, dental restoration, or the last stage extraction if the teeth cannot be maintained. This case report will discuss the treatment of primary tooth cavity lesions without pulp involvement in young children through Interim therapeutic Restoration (ITR) and strategies that need to be implemented to support the success of treatment and prevent the damage from worsening. The result showed that ITR wa successfully performed in young children with cooperative behavior to prevent more extensive tooth decay. DOI : 10.54052/jhds.v2n2.p267-278